Blended ternary positive electrode material, preparation method thereof and lithium ion battery
Simultaneous sintering of large and small particles in layers within a kiln, leveraging temperature differences, addresses the inefficiencies of current methods by enhancing uniformity and electrical properties in lithium-ion battery positive materials, thus improving production efficiency and performance.
Patent Information
- Application Number
- JP2023070453
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-11
- Filing Date
- 2023-04-21
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2043-04-21
AI Technical Summary
Current methods for preparing blended large and small particles in lithium-ion battery positive materials are time-consuming, complex, limited in production capacity, and costly, with non-uniformity leading to suboptimal electrical characteristics.
A method involving simultaneous sintering of large and small particles in layers within a kiln, utilizing temperature differences to enhance uniformity and electrical properties, using specific molecular formulas and additives, and controlled sintering parameters to improve particle uniformity and electrical characteristics.
The method results in a more uniform sintered material with improved electrical characteristics, reducing preparation time and costs while increasing production capacity.
Smart Images

Figure 0007624473000004 
Figure 0007624473000005 
Figure 0007624473000006
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a blended ternary positive electrode material, its preparation method and a lithium ion battery. [Background technology]
[0002] In recent years, with the development of new energy industry, the technology of blending large particles and small particles has been widely applied to positive electrode materials. By blending large particles and small particles, the energy density of the material can be increased and the service life of the battery can be extended.
[0003] At present, in the general blending process of large particles and small particles, the preparation of large particles and small particles needs to be sintered separately, that is, the precursor of large particles is mixed with a lithium source and an additive, and then sintered, post-treated, coated (blended), and then sintered to obtain the finished product of large particles, and the precursor of small particles is mixed with a lithium source and an additive, and then sintered, post-treated, coated (blended), and then sintered to obtain the finished product of small particles.
[0004] Therefore, the current large and small particle blending process has a long preparation time, is complicated, the production capacity is limited by the apparent density of the material, the production capacity is relatively low, and the preparation cost is relatively high.
[0005] With this in mind, the present invention has been devised. Summary of the Invention
[0006] The present invention aims to provide a blended ternary positive electrode material with improved primary particle uniformity and electrical properties, a preparation method thereof, and a lithium ion battery.
[0007] The present invention is realized as follows.
[0008] In a first aspect, the present invention provides a method for preparing a blended ternary positive electrode material, which includes the steps of: mixing a large particle precursor with a lithium source and pre-sintering to obtain a first pre-sintered material; mixing a small particle precursor with a lithium source and pre-sintering to obtain a second pre-sintered material; mixing the first pre-sintered material with an adhesive, tapping to make holes, to obtain a first lump of material to be sintered; mixing the second pre-sintered material with an adhesive, tapping to make holes, to obtain a second lump of material to be sintered; and putting the first lump of material to be sintered and the second lump of material to be sintered into a single sagger and simultaneously performing primary sintering; selects a first material placement method or a second material placement method, in the first material placement method, the first material block to be sintered is a material block having a central notch, and when placing the material, the second material block to be sintered is placed in the central notch of the first material block to be sintered so as to fill the central notch, in the second material placement method, the first material block to be sintered and the second material block to be sintered are material blocks having the same cross-sectional shape and dimensions, the second material block to be sintered is placed in a lower layer, and the first material block to be sintered is placed in an upper layer, and the molecular formulas of the large particle diameter precursor and the small particle diameter precursor are both LiNi x Mn y Co z O2, where x+y+z=1, x=0.82 to 0.84, y=0.05 to 0.07, and z=0.10 to 0.12 are satisfied, the particle size D50 of the large particle diameter precursor is 8 μm to 12 μm, and the particle size D50 of the small particle diameter precursor is 2 μm to 8 μm.
[0009] In an optional embodiment, the mass ratio of the first mass of material to be sintered to the second mass of material to be sintered is 2-3:1, and when preparing each of the first mass of material to be sintered and the second mass of material to be sintered, the mass ratio of the adhesive to the corresponding pre-sintering material is 1-3:100.
[0010] In an alternative embodiment, the tap density of the first mass of material to be sintered and the second mass of material to be sintered are both 2.0 g / cm 3 ~3.0g / cm 3 The porosity of each of the first mass of material to be sintered and the second mass of material to be sintered is set to 30% to 40%.
[0011] In an alternative embodiment, the sagger includes a rectangular bottom support plate, the bottom support plate is provided with a plurality of through holes, and no surrounding structure is provided around the periphery of the bottom support plate. The length and width of the sagger are both 320 mm to 340 mm, and the thickness is 10 mm to 20 mm. The total material placement amount of the first material block to be sintered and the second material block to be sintered is 5 kg to 10 kg for the sagger. When the first material placement method is adopted, the first material block to be sintered is a material block having a central notch and a rectangular cross-sectional shape, and the length and width of the rectangular cross-section are both 5 kg to 10 kg. both are 250mm to 350mm, the central cutout is a rectangular cutout, the length and width of the central cutout are both 90mm to 110mm, and the second material block to be sintered is made to match the shape and dimensions of the central cutout. When the second material arrangement method is adopted, the first material block to be sintered and the second material block to be sintered are both material blocks having a rectangular cross-sectional shape, the length and width of the rectangular cross-section are both 250mm to 350mm, and the thickness of the first material block to be sintered and the second material block to be sintered are both less than 20mm.
[0012] In an alternative embodiment, the temperature of the primary sintering is 725° C. to 740° C., and the sintering time of the primary sintering is 10 hours to 12 hours.
[0013] In an optional embodiment, additives are added in the preparation of the first pre-sintering material and the second pre-sintering material, respectively, and the additive is at least one selected from ZrO2, SbO2, SrCO3, TiO2 and MgO. In the preparation of the first pre-sintering material and the second pre-sintering material, respectively, the molar ratio of the precursor to the lithium source is 1:1.02-1.06, the mass ratio of the additive to the precursor is 0.1-10:100, the pre-sintering temperature is 500°C-600°C, and the pre-sintering time is 4h-6h.
[0014] In an alternative embodiment, after primary sintering, the sintered material is crushed and then subjected to post-processing and secondary sintering, where crushing is to break up the agglomerated material and post-processing includes washing, filtering and drying in sequence.
[0015] In an optional embodiment, the secondary sintering is to mix the post-treated material with a coating agent and sinter it at a temperature condition of 550°C to 650°C for 8h to 10h, the coating agent is at least one selected from Al2O3, Co3O4, H3BO3, TiO2 and MgO, and the mass ratio of the coating agent to the post-treated material is 0.2-0.5:100.
[0016] In a second aspect, the present invention provides a blended ternary positive electrode material, the blended ternary positive electrode material being prepared by the preparation method according to any one of the above embodiments.
[0017] In a third aspect, the present invention provides a lithium-ion battery prepared with the blended ternary positive electrode material according to the above embodiment.
[0018] The present invention has the following beneficial effects: Using temperature-sensitive precursor material as raw material, firstly, the precursor of large particles and the precursor of small particles are mixed with a lithium source to perform pre-sintering to obtain the first pre-sintering material and the second pre-sintering material, respectively, and then mixed with an adhesive, tapped and pitted to obtain the first material block to be sintered and the second material block to be sintered, and the first material block to be sintered and the second material block to be sintered are put into the same sagger to perform primary sintering at the same time. A method of disposing materials by dividing into the peripheral part and the center part or dividing into upper and lower layers is adopted, such that the first pre-sintering material is disposed in the peripheral part or the upper layer, and the second pre-sintering material is disposed in the center part or the lower layer. During the sintering process, the temperature of the center part is lower than that of the peripheral part, and the temperature of the lower layer is lower than that of the upper layer, so that the material disposing method according to the present application can adapt to the temperature distribution, disposing the material of large particles in the higher temperature area and the material of small particles in the lower temperature area, thus improving the uniformity of the primary particles and improving the electrical properties of the material.
[0019] Compared with the prior art, the present invention adopts a layer or region sintering technology when mixing materials, thereby realizing the simultaneous sintering of large particles and small particles in the same sagger, making full use of the temperature difference in the temperature field of the kiln itself, compensating for the defects of the kiln itself, and preparing large-particle sintering materials and small-particle sintering materials with good sintering effects, so that in the later process, the large-particle sintering materials and small-particle sintering materials can be mixed more uniformly. [Brief description of the drawings]
[0020] In order to more clearly describe the technical solutions of the embodiments of the present invention, the drawings necessary for describing the embodiments are briefly described below. The drawings described are only for illustrating some embodiments of the present invention, and are not intended to limit the scope. Those skilled in the art can obtain other related drawings based on these drawings without using inventive abilities. [Figure 1] FIG. 2 is a schematic diagram showing the temperature difference between the inner and outer parts of a sagger. [Diagram 2] FIG. 1 is a schematic diagram showing the temperature difference in the upper layer of a sagger. [Diagram 3] FIG. 2 is a schematic diagram of a sagger viewed from a first angle. [Figure 4] FIG. 4 is a schematic diagram of the sagger as viewed from a second angle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] In order to more clearly explain the objectives, technical solutions and advantages of the embodiments of the present invention, the technical solutions in the embodiments of the present invention are described below clearly and completely. In the embodiments, the specific conditions are not specified, and the operations can be carried out under conventional conditions or conditions recommended by the manufacturer. For reagents or equipment whose manufacturers are not specified, conventional products available on the market can be used.
[0022] During the sintering process of the materials, due to the defects of the sintering equipment itself, even if the materials are in the same sagger, there will be obvious temperature differences between the more central and more peripheral parts in the sagger, and between the more inner and outer parts in the sagger (see Figures 1 and 2). The surface temperature difference of the ternary material is about 20K. After sintering, the primary particles of the material are not uniform, and the performance varies, which reduces the performance of the blended material.
[0023] The embodiment of the present invention provides a method for preparing a blended ternary positive electrode material, which uses a special primary sintering method for the precursor in consideration of the sintering temperature sensitivity of large particles and small particles, and uses a process of simultaneously sintering large particles and small particles, which can compensate for the temperature difference in the temperature field during sintering, and improve the uniformity of the primary particles and the electrical properties of the product. Specifically, the method includes the following steps:
[0024] S1. Pre-sintering
[0025] A large particle size precursor is mixed with a lithium source and pre-sintered to obtain a first pre-sintered material, and a small particle size precursor is mixed with a lithium source and pre-sintered to obtain a second pre-sintered material. In the pre-sintering process, the large particle size precursor and the small particle size precursor are sintered separately, and there is no limitation on the process parameters.
[0026] The material to be treated in the sintering process according to the embodiment of the present invention is a temperature-sensitive high nickel material, and the molecular formula of both the large particle size precursor and the small particle size precursor is LiNi x Mn y Co z O2 (satisfying x+y+z=1, x=0.82-0.84, y=0.05-0.07, z=0.10-0.12), the large particle size precursor has a particle size D50 of 8 μm-12 μm and a span = 0.9-1.3 (span represents the width of the material particle size distribution), and the small particle size precursor has a particle size D50 of 2 μm-8 μm and a span = 0.9-1.3.
[0027] The primary sintering temperatures of the large and small particles of different series of precursors are shown in Table 1. The above high nickel material selected by the inventors is "83 Nickel (compound LiNi x Mn y Co z O2 (x+y+z=1), the molar ratio of nickel to the total content of Ni, Co, and Mn is 83%, and it has a relatively sharp response to temperature. The sintering temperature difference between large and small particles can adapt to the temperature difference in the temperature field. Therefore, the temperature difference in the kiln is used to sinter large and small particles simultaneously.
[0028] [Table 1]
[0029] In some embodiments, additives are added during pre-sintering to improve the performance of the final product. Additives are added during the preparation of both the first pre-sintered material and the second pre-sintered material. The additives are at least one selected from ZrO2, SbO2, SrCO3, TiO2, and MgO. The addition of the additives can contribute to improving the electrical properties of the final product.
[0030] In addition, in the preparation of the first pre-sintering material and the second pre-sintering material, the molar ratio of the precursor to the lithium source is 1:1.02-1.06, the mass ratio of the additive to the precursor is 0.1-10:100, the temperature of pre-sintering is 500°C-600°C, and the time of pre-sintering is 4h-6h. In the preparation of the first pre-sintering material and the second pre-sintering material, the relevant parameters are in the above ranges, so as to ensure the performance of the final product.
[0031] S2. Primary sintering
[0032] The first pre-sintering material is mixed with adhesive, tapped, and a hole is formed to obtain the first lump of material to be sintered; the second pre-sintering material is mixed with adhesive, tapped, and a hole is formed to obtain the second lump of material to be sintered; the first lump of material to be sintered and the second lump of material to be sintered are put into the same sagger and simultaneously sintered for the first time. The tapping and sintering method can further improve the sintering effect, sintering speed, and production capacity. The purpose of the hole formation is to maintain a certain porosity in the material and quickly release gases such as carbon dioxide generated by the adhesive during sintering.
[0033] Specifically, the adhesive may be a common adhesive such as PVA, PEC, or PVP.
[0034] The material arrangement method for the primary sintering can be selected from the first material arrangement method or the second material arrangement method. The first material arrangement method is a method of arranging materials in separate areas such as the periphery and the center, and the second material arrangement method is a method of arranging materials in upper and lower layers. The two material arrangement methods are well adapted to the temperature field distribution in the sagger, and large-particle materials are arranged in the periphery or upper layer, and small-particle materials are arranged in the center or lower layer.
[0035] Specifically, in the case of the first material placement method, the first material block to be sintered is a material block having a notch in the center, and when placing the material, the second material block to be sintered is placed in the notch in the center of the first material block to be sintered so as to fill the notch in the center. The second material block to be sintered may be of a size that fits perfectly into the notch in the center, or may be substantially smaller than the notch in the center.
[0036] Specifically, in the second material arrangement manner, the first and second material blocks to be sintered are material blocks with the same cross-sectional shape and dimensions, and the second material block to be sintered is arranged in a lower layer, and the first material block to be sintered is arranged in an upper layer. The second material block to be sintered is arranged in the lower layer, contacts the sagger, and is located in an area with a relatively low temperature. The first material block to be sintered is placed in the upper layer, and is located in an area with a relatively high temperature. The layered sintering can make better use of the sintering space of the kiln and improve the material arrangement amount of the sagger.
[0037] The inventors optimized the parameters of the primary sintering, and set the mass ratio (blending ratio) of the first material block to be sintered and the second material block to be sintered to 2 to 3: 1. When preparing each of the first material block to be sintered and the second material block to be sintered, the mass ratio of the adhesive used to the corresponding pre-sintering material was set to 1 to 3: 100, and the tap density of each of the first material block to be sintered and the second material block to be sintered was set to 2.0 g / cm. 3 ~3.0g / cm 3 The porosity of the first and second material blocks to be sintered is 30% to 40%, the temperature of the primary sintering is 725°C to 740°C, and the sintering time of the primary sintering is 10h to 12h. By further controlling the parameters of the primary sintering, the uniformity of the sintering can be improved, and a sintered material with more uniform particles can be obtained.
[0038] Specifically, the mass ratio of the first material block to be sintered to the second material block to be sintered can be 2:1, 2.5:1, 3:1, etc., and within this range, the tap density is improved and the cycle performance is relatively good. The tap density is 2.0 g / cm 3 , 2.5g / cm 3 , 3.0g / cm 3 and the porosity can be 30%, 35%, 40%, and so on.
[0039] In some embodiments, the sagger includes a rectangular bottom support plate, the bottom support plate is provided with a number of through holes, and the bottom support plate is provided with no surrounding structure. The combination of the sagger without surrounding structure and the tapping and sintering scheme, as well as the area partitioning and sintering scheme, can further reduce the material preparation cost and improve the product performance (cycle life). The sagger without surrounding structure is a plate-like structure, in which a number of through holes are provided, and the holes can be elongated holes or square holes distributed in a matrix, as shown in Figures 3 and 4.
[0040] To achieve fine control, the inventors optimized the material placement for a sagger of a specific size, but other sizes can be adjusted proportionally. For a sagger with a length and width of 320mm to 340mm (e.g., 330mm) and a thickness of 10mm to 20mm, the total material placement amount of the first and second material blocks to be sintered is 5Kg to 10Kg. The placements when the first and second material placement methods are adopted are as follows: (1) When the first material arrangement method is adopted, the first material block to be sintered is a material block having a central notch and a rectangular cross-sectional shape, the length and width of the rectangular cross-section are both 250mm to 350mm (for example, the length and width are both 250mm, 300mm, 350mm, etc., and the length and width may be the same or different), the central notch is a rectangular notch, the length and width of the central notch are both 90mm to 110mm (for example, 90mm, 100mm, 110mm, etc.), and the second material block to be sintered is made to match the shape and dimensions of the central notch. The thicknesses of the two types of material blocks can be appropriately increased or decreased in consideration of the load capacity of the kiln itself. (2) When the second material arrangement method is adopted, the first material block to be sintered and the second material block to be sintered are both material blocks having a rectangular cross-sectional shape, and the length and width of the rectangular cross-section are both 250 mm to 350 mm (for example, the length and width are both 250 mm, 300 mm, 350 mm, etc., and the length and width may be the same or different), and the thickness of the first material block to be sintered and the second material block to be sintered are both less than 20 mm, which can be appropriately adjusted taking into account the load-bearing capacity of the kiln itself and the required proportion of the material.
[0041] S3. Secondary sintering
[0042] In an alternative embodiment, after the primary sintering, the sintered material is crushed and then subjected to post-treatment and secondary sintering, and the finished cathode material is obtained after the secondary sintering.
[0043] Specifically, grinding is the breaking up of chunks of material without affecting the particle size of the particles themselves, using a roll grinder to grind coarsely and a mechanical mill or other equipment to grind finely, although the precursor particles as a whole are relatively small in size, so the grinding does not affect the particle size of the particles themselves.
[0044] Specifically, the post-treatment includes sequentially washing with water, filtering and drying, and removing surface impurities by washing with water and filtering to obtain a clean intermediate positive electrode material for secondary sintering.
[0045] Furthermore, the secondary sintering is to mix the post-treated material with a coating agent and sinter it at a temperature condition of 550 ° C to 650 ° C for 8h to 10h. The coating agent is at least one selected from Al2O3, Co3O4, H3BO3, TiO2 and MgO. The mass ratio of the coating agent to the post-treated material is 0.2 to 0.5:100. By adding the coating agent, the performance of the positive electrode material can be further improved, and it is preferable that the type and amount of the coating agent be within the above range.
[0046] The embodiment of the present invention provides a blended ternary positive electrode material prepared by the above preparation method, the positive electrode material comprises large particles and small particles, and through the improvement of the sintering process, the particle uniformity of the positive electrode material product is high, and the electrical properties of the material are better, and the positive electrode material can be used to prepare a lithium-ion battery.
[0047] The features and performance of the present invention will be described in more detail below with reference to examples.
[0048] Example 1 In this example, a blended ternary positive electrode material was prepared by a preparation method including the following steps:
[0049] (1) Selection of precursor The precursor has the molecular formula LiNi 83 Mn 06 Co 11 It was O2. The large particle precursor had a particle size D50=10 μm and a span=1.0. The small particle precursor had a particle size D50=5 μm and a span=1.0.
[0050] (2) Pre-sintering The large particle size precursor, lithium hydroxide, ZrO2, and TiO2 (the mass ratio of the additives ZrO2 and TiO2 was 1:1) were mixed and pre-sintered to obtain a first pre-sintered material, in which the molar ratio of the large particle size precursor to the lithium source was 1:1.03, the mass ratio of the additive to the large particle size precursor was 0.4:100, the pre-sintering temperature was 550°C, and the pre-sintering time was 5h. The small particle size precursor, lithium hydroxide, ZrO2, and TiO2 (the mass ratio of the additives ZrO2 and TiO2 was 1:1) were mixed and pre-sintered to obtain a second pre-sintered material, in which the molar ratio of the small particle size precursor to the lithium source was 1:1.03, the mass ratio of the additive to the small particle size precursor was 0.4:100, the pre-sintering temperature was 550°C, and the pre-sintering time was 5h.
[0051] (3) Primary sintering The first pre-sintering material and the adhesive PVA are mixed and tapped to form holes to obtain a first mass of material to be sintered. The mass ratio of the adhesive to the pre-sintering material is 2:100, and the tap density is 2.5g / cm. 3 and the porosity was set to 35%. The second pre-sintering material is mixed with the adhesive PVA, tapped, and holes are made to obtain a second pre-sintering material mass, with the mass ratio of the adhesive to the pre-sintering material being 2:100 and the tap density being 2.5g / cm 3 and the porosity was set to 35%. The first and second sintering material blocks were placed in the same sagger and subjected to primary sintering at the same time. The mass ratio of the first and second sintering material blocks was 2.5:1, the primary sintering temperature was 732°C, and the sintering time was 11 hours. Material arrangement method The total amount of material placed in the first and second to-be-sintered material blocks was 6 kg in a sagger with a length and width of 330 mm each and a thickness of 10 mm. The material was placed using the first material placement method. The first to-be-sintered material block had a rectangular cross-sectional shape with a central notch, and the length and width of the rectangular cross-section were both 300 mm, and the central notch was a rectangular notch, and the length and width of the central notch were both 100 mm. The second to-be-sintered material block had a length and width of 100 mm each, which matched the shape and dimensions of the central notch.
[0052] (4) Secondary sintering After the primary sintering, the sintered material was crushed, and then post-processed and secondary sintered. After the secondary sintering, the finished cathode material was obtained. The post-processing included washing with water, filtering and drying in sequence. For the secondary sintering, the post-processed material was mixed with the coating material Al2O3 and sintered at a temperature of 620℃ for 8h. The mass ratio of the coating material to the post-processed material was 0.3:100.
[0053] Example 2 In this example, a blended ternary positive electrode material was prepared by a preparation method including the following steps:
[0054] (1) Selection of precursor The precursor has the molecular formula LiNi 83 Mn 06 Co 11 It was O2. The large particle precursor had a particle size D50=8 μm and a span=0.9. The small particle precursor had a particle size D50=2 μm and a span=0.9.
[0055] (2) Pre-sintering The large particle size precursor, lithium hydroxide, ZrO2, and TiO2 (the mass ratio of the additives ZrO2 and TiO2 was 1:1) were mixed and pre-sintered to obtain a first pre-sintered material, in which the molar ratio of the large particle size precursor to the lithium source was 1:1.02, the mass ratio of the additive to the large particle size precursor was 0.1:100, the pre-sintering temperature was 500°C, and the pre-sintering time was 6h. The small particle size precursor, lithium hydroxide, ZrO2, and TiO2 (the mass ratio of the additives ZrO2 and TiO2 was 1:1) were mixed and pre-sintered to obtain a second pre-sintered material, in which the molar ratio of the small particle size precursor to the lithium source was 1:1.02, the mass ratio of the additive to the small particle size precursor was 0.1:100, the pre-sintering temperature was 500°C, and the pre-sintering time was 6h.
[0056] (3) Primary sintering The first pre-sintering material and the adhesive PVA are mixed and tapped to form holes to obtain a first mass of material to be sintered. The mass ratio of the adhesive to the pre-sintering material is 1:100, and the tap density is 2.0 g / cm. 3 and the porosity was set to 35%. The second pre-sintering material is mixed with the adhesive PVA, tapped, and holes are made to obtain a second pre-sintering material mass, with the mass ratio of the adhesive to the pre-sintering material being 1:100 and the tap density being 2.0 g / cm 3 and the porosity was set to 40%. The first and second sintering material blocks were placed in the same sagger and subjected to primary sintering at the same time. The mass ratio of the first and second sintering material blocks was 2:1, the primary sintering temperature was 725°C, and the primary sintering time was 12 hours. Material arrangement method The total amount of material placed in the first and second to-be-sintered material blocks was 5 kg in a sagger with a length and width of 330 mm each and a thickness of 10 mm. The material was placed using the first material placement method. The first to-be-sintered material block had a rectangular cross-sectional shape with a central notch, and the length and width of the rectangular cross-section were both 250 mm, and the central notch was a rectangular notch, and the length and width of the central notch were both 90 mm. The second to-be-sintered material block had a length and width of 90 mm each, which matched the shape and dimensions of the central notch.
[0057] (4) Secondary sintering After the primary sintering, the sintered material was crushed, and then post-processed and secondary sintered. After the secondary sintering, the finished cathode material was obtained. The post-processing included washing with water, filtering and drying in sequence. For the secondary sintering, the post-processed material was mixed with the coating material Al2O3 and sintered at a temperature of 550℃ for 10h. The mass ratio of the coating material to the post-processed material was 0.2:100.
[0058] Example 3 In this example, a blended ternary positive electrode material was prepared by a preparation method including the following steps:
[0059] (1) Selection of precursor The precursor has the molecular formula LiNi 83 Mn 06 Co 11 It was O2. The large particle precursor had a particle size D50=12 μm and a span=1.3. The small particle precursor had a particle size D50=8 μm and a span=1.3.
[0060] (2) Pre-sintering The large particle size precursor, lithium hydroxide, ZrO2, and TiO2 (the mass ratio of the additives ZrO2 and TiO2 was 1:1) were mixed and pre-sintered to obtain a first pre-sintered material, in which the molar ratio of the large particle size precursor to the lithium source was 1:1.06, the mass ratio of the additive to the large particle size precursor was 1.0:100, the pre-sintering temperature was 600°C, and the pre-sintering time was 4h. The small particle size precursor, lithium hydroxide, ZrO2, and TiO2 (the mass ratio of the additives ZrO2 and TiO2 was 1:1) were mixed and pre-sintered to obtain a second pre-sintered material, in which the molar ratio of the small particle size precursor to the lithium source was 1:1.06, the mass ratio of the additive to the small particle size precursor was 1.0:100, the pre-sintering temperature was 600°C, and the pre-sintering time was 4h.
[0061] (3) Primary sintering The first pre-sintering material and the adhesive PVA are mixed and tapped to form holes to obtain a first mass of material to be sintered. The mass ratio of the adhesive to the pre-sintering material is 3:100, and the tap density is 3.0 g / cm. 3 and the porosity was set to 35%. The second pre-sintering material is mixed with the adhesive PVA, tapped, and holes are made to obtain a second pre-sintering material mass, with the mass ratio of the adhesive to the pre-sintering material being 3:100 and the tap density being 3.0g / cm 3 and the porosity was set to 30%. The first and second sintering material blocks were placed in the same sagger and subjected to primary sintering at the same time. The mass ratio of the first and second sintering material blocks was 3:1, the primary sintering temperature was 740°C, and the primary sintering time was 10 hours. Material arrangement method The total amount of material placed in the first and second to-be-sintered material blocks was 10 kg in a sagger with a length and width of 330 mm each and a thickness of 10 mm. The material was placed using the first material placement method. The first to-be-sintered material block had a rectangular cross-sectional shape with a central notch, and the length and width of the rectangular cross-section were both 350 mm, and the central notch was a rectangular notch, and the length and width of the central notch were both 110 mm. The second to-be-sintered material block had a length and width of 110 mm each, which matched the shape and dimensions of the central notch.
[0062] (4) Secondary sintering After the primary sintering, the sintered material was crushed, and then post-processed and secondary sintered. After the secondary sintering, the finished cathode material was obtained. The post-processing included washing with water, filtering and drying in sequence. For the secondary sintering, the post-processed material was mixed with the coating material Al2O3 and sintered at a temperature of 650℃ for 8h. The mass ratio of the coating material to the post-processed material was 0.5:100.
[0063] Example 4 The blended ternary positive electrode material prepared by the preparation method of this embodiment differs from that of Example 1 only in the following points: In step (3), the second material arrangement method is adopted, and the first and second material blocks to be sintered are both rectangular in cross section, and the length and width of the rectangular cross section are both 300 mm, and the parameters and amounts of the first and second material blocks to be sintered are unchanged.
[0064] Examples 5 to 8 The blended ternary positive electrode materials prepared by the preparation method of this embodiment are different from those of Example 4 only in the following points: In Examples 5 to 8, in step (3), the mass ratios of the first mass of material to be sintered and the second mass of material to be sintered were 1:1, 2:1, 3:1, and 4:1, respectively.
[0065] In Examples 4 to 8, the thickness of the large particle material block varied slightly depending on the amount used, but was always 15 mm to 20 mm, and the thickness of the small particle material block varied slightly depending on the amount used, but was always 20 mm to 25 mm.
[0066] Comparative Example 1 The blended ternary positive electrode material prepared by the preparation method of this comparative example is different from that of Example 1 only in the following points: In step (3), the first and second pre-sintered material blocks are sintered separately so as to be arranged in a sagger with the same thickness, that is, 6 kg of the first pre-sintered material block and 5 kg of the second pre-sintered material block are separately placed in a sagger and sintered separately, the first pre-sintered material block is sintered at a sintering temperature of 732°C, and the second pre-sintered material block is sintered at a sintering temperature of 727°C, and the sintering time is the same as that of Example 1. After sintering, the sintered materials are mixed uniformly.
[0067] Comparative Example 2 The blended ternary positive electrode material prepared by the preparation method of this comparative example differs from that of Example 1 only in the following points: x Mn y Co z The NCM85 nickel precursor, O2 (x+y+z=1, x=0.85, y=0.05–0.07, z=0.08–0.10), was employed.
[0068] Comparative Example 3 The blended ternary positive electrode material prepared by the preparation method of this comparative example differs from that of Example 1 only in the following points: x Mn y Co z The NCM88 nickel precursor, O2 (x+y+z=1, x=0.88, y=0.05–0.07, z=0.1–0.12), was employed.
[0069] Comparative Example 4 The blended ternary positive electrode material prepared by the preparation method of this comparative example differs from that of Comparative Example 1 only in the following points: x Mn yCo z The NCM85 nickel precursor, O2 (x+y+z=1, x=0.85, y=0.05~0.07, z=0.08~0.10), was used, and the first sintered material block was sintered at a temperature of 750°C, and the second sintered material block was sintered at a temperature of 720°C.
[0070] Comparative Example 5 The blended ternary positive electrode material prepared by the preparation method of this comparative example differs from that of Comparative Example 1 only in the following points: x Mn y Co z The NCM88 nickel precursor, O2 (x+y+z=1, x=0.88, y=0.05-0.07, z=0.1-0.12), was used, and the first sintered material block was sintered at a temperature of 740°C, and the second sintered material block was sintered at a temperature of 710°C.
[0071] Test experiment example 1
[0072] How we tested (1) Coin cell fabrication: Nickel ternary positive electrode material, Super P, and PVDF adhesive were mixed uniformly in NMP solvent in a mass ratio of 90:5:5 to prepare a slurry with a cobalt content of 45%. The slurry was evenly applied to an aluminum foil and dried with air at 60°C for 3 hours. The plate was placed in a vacuum oven and dried at 120°C for 12 hours. The dried plate was punched out to form a circular plate with a diameter of 12 mm. This plate was used as the positive electrode, Celgard 2400 was used as the separator, metallic lithium pieces were used as the negative electrode, and 1M (mol / L) LiPF6 was dissolved in a mixed electrolyte of EMC:DC:DMC=1:1:1 to prepare the electrolyte, thereby manufacturing a half coin cell.
[0073] (2) Initial charge / discharge test: An initial charge / discharge test was performed on the coin-type batteries manufactured using the high-nickel ternary positive electrode materials obtained in each of Examples 1 to 8 and Comparative Examples 1 to 5. The test was performed at a rate of 0.1C (theoretical capacity of 200mAh / g) at 2.8V to 4.3V, and the batteries were first charged at 0.1C and then discharged at 0.1C, thereby obtaining a charge / discharge curve and an initial charge / discharge capacity, and the results are shown in Table 3 below.
[0074] (3) High-temperature cycle performance test: A cycle performance test at high temperature (45°C) was carried out on the coin-type batteries manufactured using the high-nickel ternary positive electrode materials obtained in each of Examples 1 to 8 and Comparative Examples 1 to 5. As a test method, after the initial charge / discharge at 2.8V to 4.3V and 0.1C (nominal capacity is 200mAh / g), a charge / discharge test was carried out for 50 cycles at a rate of 1C, and the capacity retention rate after 50 cycles under high-temperature conditions was obtained, and the results are shown in Table 3 below.
[0075] The performance of the positive electrode materials prepared according to Examples 5 to 8 was tested, and the results are shown in Table 2.
[0076] [Table 2]
[0077] In the above experiment, the material placement condition was 6 kg of material placement amount. In theory, if the kiln allows a larger amount of material placement, the material placement amount can be increased, but the blend ratio should be large particles:small particles = 2:1, 3:1.
[0078] The electrical properties of the positive electrode materials obtained in each of the examples and comparative examples were tested, and the results are shown in Table 3.
[0079] [Table 3]
[0080] 0.1CC refers to the specific charging capacity at a rate of 0.1C. 0.1CD refers to the specific discharge capacity at a rate of 0.1C. Eff is the ratio of the initial discharge specific capacity to the charge specific capacity at a rate of 0.1C. HT-Cap refers to the specific charge / discharge capacity at a rate of 1C under temperature conditions of 45°C ± 5°C. HT-50cy refers to the capacity retention rate after 50 cycles of charging and discharging at a rate of 1C under temperature conditions of 45°C ± 5°C.
[0081] The above is only a preferred embodiment of the present invention, and is not intended to limit the present invention. Those skilled in the art may have various modifications and changes to the present invention. As long as it does not deviate from the spirit and scope of the present invention, any modifications, equivalent replacements, improvements, etc., are within the protection scope of the present invention.
Claims
1. Mixing a large particle size precursor and a lithium source and pre-sintering to obtain a first pre-sintered material, and mixing a small particle size precursor and a lithium source and pre-sintering to obtain a second pre-sintered material; mixing the first pre-sintering material with an adhesive, tapping the mixture, and forming a hole to obtain a first lump of material to be sintered; mixing the second pre-sintering material with an adhesive, tapping the mixture, and forming a hole to obtain a second lump of material to be sintered; and putting the first lump of material to be sintered and the second lump of material to be sintered into a single sagger to perform primary sintering at the same time; Including, The material placement method for the primary sintering is selected from a first material placement method and a second material placement method. In the case of the first material placement method, the first material block to be sintered is a material block having a notch in the center, and when placing the material, the second material block to be sintered is placed in the notch in the center of the first material block to be sintered so as to fill the notch in the center. In the case of the second material placement method, the first material block to be sintered and the second material block to be sintered are made into material blocks having the same cross-sectional shape and dimensions, and the second material block to be sintered is placed in a lower layer, and the first material block to be sintered is placed in an upper layer. The molecular formula of the large particle diameter precursor and the small particle diameter precursor are both LiNi x Mn y Co z O 2 where x+y+z=1, x=0.82 to 0.84, y=0.05 to 0.07, and z=0.10 to 0.12 are satisfied, the particle size D50 of the large particle size precursor is 8 μm to 12 μm, and the particle size D50 of the small particle size precursor is 2 μm to 8 μm, The mass ratio of the first mass of material to be sintered to the second mass of material to be sintered is 2 to 3:1; 1. A method for preparing a blended ternary positive electrode material, comprising:
2. When preparing each of the first mass of material to be sintered and the second mass of material to be sintered, the mass ratio of the adhesive to the corresponding pre-sintered material is set to 1 to 3:
100.
2. The method according to claim 1 .
3. The tap density of the first material mass to be sintered and the second material mass to be sintered are both 2.0 g / cm 3 ~3.0g / cm 3 and the porosity of each of the first mass of material to be sintered and the second mass of material to be sintered is set to 30% to 40%.
3. The method according to claim 2 .
4. The sagger includes a rectangular bottom support plate, the bottom support plate is provided with a plurality of through holes, and no surrounding structure is provided around the periphery of the bottom support plate; For a sagger having a length and a width of 320 mm to 340 mm and a thickness of 10 mm to 20 mm, the total material placement amount of the first material mass to be sintered and the second material mass to be sintered is 5 kg to 10 kg; When the first material arrangement method is adopted, the first material block to be sintered is a material block having a central notch and a rectangular cross-sectional shape, the length and width of the rectangular cross-section are both 250 mm to 350 mm, the central notch is a rectangular notch, the length and width of the central notch are both 90 mm to 110 mm, and the second material block to be sintered is adapted to match the shape and dimensions of the central notch, When the second material arrangement method is adopted, the first material block to be sintered and the second material block to be sintered are both material blocks having a rectangular cross-sectional shape, the length and width of the rectangular cross-section are both 250 mm to 350 mm, and the thickness of the first material block to be sintered and the second material block to be sintered are both less than 20 mm.
4. The method according to claim 3 .
5. The primary sintering temperature is set to 725°C to 740°C, and the primary sintering time is set to 10 hours to 12 hours. The process according to any one of claims 1 to 4.
6. In the preparation of the first pre-sintered material and the second pre-sintered material, an additive is added, and the additive is ZrO 2 , SbO 2 , SrCO 3 , TiO 2 and MgO, In the preparation of the first pre-sintered material and the second pre-sintered material, the molar ratio of the precursor to the lithium source is 1:1.02-1.06, the mass ratio of the additive to the precursor is 0.1-10:100, the pre-sintering temperature is 500°C-600°C, and the pre-sintering time is 4h-6h.
2. The method according to claim 1 .
7. After the primary sintering, the sintered material is crushed and then subjected to post-treatment and secondary sintering; The grinding step is to break up clumps of material; The post-treatment includes washing with water, filtering and drying, which are performed in sequence.
2. The method according to claim 1 .
8. The secondary sintering is to mix the post-treated material with the coating agent and sinter it at a temperature of 550°C to 650°C for 8h to 10h; The coating agent is Al 2 O 3 , Co 3 O 4 , H 3 B.O. 3 , TiO 2 and MgO, and the mass ratio of the coating agent to the post-treated material is 0.2-0.5:
100.
8. The method according to claim 7 .
Citation Information
Patent Citations
Transition metal-containing composite hydroxide particle and manufacturing method therefor, cathode active material for nonaqueous electrolyte secondary battery and manufacturing method therefor, and nonaqueous electrolyte secondary battery
JP2019119662A
Method for producing a positive electrode active material precursor for lithium secondary batteries
JP2022510305A
Positive electrode active material, method for manufacturing same, positive electrode material comprising same, positive electrode, and lithium secondary battery
WO2022139516A1